Effects of Competition with Four Nonnative Salmonid Species on Atlantic Salmon from Three Populations. Issue 5 (17th August 2015) - Houde, Aimee Lee S.; Wilson, Chris C.; Neff, Bryan D.
Abstract: The presence of ecologically similar nonnative species may impede recovery efforts for native species. We assessed the survival and growth of juvenile Atlantic Salmon Salmo salar from three populations (LaHave River, Sebago Lake, and Lac Saint‐Jean) in the presence of four naturalized nonnative salmonid competitors. The three populations are being used for reintroduction efforts in Lake Ontario, where Atlantic Salmon are extirpated. Juvenile Atlantic Salmon were placed into artificial stream tanks with combinations of juvenile Brown Trout S. trutta, Rainbow Trout Oncorhynchus mykiss, Chinook Salmon O. tshawytscha, and Coho Salmon O. kisutch . Survival of all three Atlantic Salmon populations was lower in the presence of Brown Trout; growth was lower in the Brown Trout treatment and in the multispecies treatment. In contrast, Atlantic Salmon survival and growth were not negatively impacted by the presence of Chinook Salmon, Rainbow Trout, or Coho Salmon. Based on measurements of circulating hormones, Atlantic Salmon were not chronically stressed and did not show a change in social status after 10 months in the artificial stream tanks. Our results support the theory that differences in aggression and niche overlap can influence competitive outcomes and suggest that tributaries containing Brown Trout should be avoided during Atlantic Salmon reintroduction into Lake Ontario.